Audit Quality and Tax Avoidance: The Role of Independent Commissioners and Audit Committee's Financial Expertise - Amelia Rizqia; Anies Lastiati (Journal of Accounting Auditing and Business, 2021)
Abstract: This study aims to examine the effect of audit quality on tax avoidance. It further examines whether an independent board of commissioners and the audit committee's expertise affect the relationship between audit quality and tax avoidance. The study observed manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the Malaysia Stock Exchange in 2018. Tax avoidance is measured by abnormal book-tax difference, while audit quality is proxied by Big Four-accounting firm and the audit tenure. The test results show that Big Four firms lower the tax avoidance level done by corporations, but not audit tenure. Furthermore, results also show that the audit committee's financial background weakens the relationship between audit quality and tax avoidance, but not an independent board of commissioners. The results are consistently found in both countries examined. The accounting firm that audits the company's financial statements gives an impact on the displayed actual company value, but not with audit committee's expertise which ineffective in carrying out its supervisory function without an understanding of the company's operational and business activities; thus the diversity of audit committee backgrounds is still needed. Furthermore, regulators should consider adopting a policy related to the estimated useful life of assets to minimise the gaps between accounting regulations and tax regulations